Membrane-bound CC chemokine inhibitor 35K provides localized inhibition of CC chemokine activity in vitro and in vivo. - Bursill, C; Cash, J; Channon, K; Greaves, D (2006)
CC chemokines mediate mononuclear cell recruitment and activation in chronic inflammation. We have shown previously that gene transfer using recombinant adenoviruses, encoding a soluble CC chemokine-binding protein of vaccinia virus 35K, can dramatically reduce atherosclerosis and vein graft remodeling in apolipoprotein E knockout mice. In this study, we report the development of a membrane-bound form of 35K (m35K), tagged with GFP, which allows for localized, broad-spectrum CC chemokine blockade. In vitro experiments indicate that m35K-expressing cells no longer undergo CC chemokine-induced chemotaxis, and m35K-expressing cells can locally deplete the CC chemokines RANTES (CCL5) and MIP-1alpha (CCL3) from supernatant medium. This sequestration of CC chemokines can prevent chemotaxis of bystander cells to CC, but not CX(3)C chemokines. Intraperitoneal injection of mice with an adenovirus-encoding m35K leads to a significant (44%) decrease in leukocyte recruitment into the peritoneal cavity in a sterile peritonitis model. Intravenous adenovirus-encoding m35K delivery leads to m35K expression in hepatocytes, which confers significant protection against liver damage (75% reduction in liver enzymes) in a Con A-induced hepatitis model. In summary, we have generated a membrane-bound CC chemokine-binding protein (m35K) that provides localized broad-spectrum CC chemokine inhibition in vitro and in vivo. m35K may be a useful tool to study the role of CC chemokines in leukocyte trafficking and block the recruitment of monocytes in chronic inflammation.